Pengukuran kinerja green manufacturing pada industri tahu sumedang untuk meningkatkan kinerja terhadap lingkungan menggunakan GSCOR dan LCA - Totok Pujianto; Anas Bunyamin; Salma Wafiyyah (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
The application of an environmentally sound industry is one of the environmental conservation issues and a global issue in the industry. The application of an environmentally sound industry can be implemented in the Green Manufacturing system. The tofu industry in the production process uses a high volume of water, resulting in a high volume of liquid waste, which can pollute the environment. The problem with the Sari Kedelai industry is that there has not been a performance measurement on the environment and an analysis of the resulting impact. This study aims to measure the performance of Green Manufacturing with the GSCOR (Green Supply Chain Operations Reference) and LCA (Life Cycle Assessment) methods as well as formulate suggestions for improvements to the Sari Kedele industry in the context of implementing Green Manufacturing. The results of performance measurement using the GSCOR method in the Sari Kedele industry has a value of 79.78 which was included in the good category. Environmental impact analysis is assessed with a focus on GHG emissions (Greenhouse Gases) that uses LCA with an ISO 14040 approach resulting in a GHG emission value of CO2-eq/kg tofu of 3.7107.